Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

Climate Change Education Curriculum for Nigeria Tertiary Education System - Dada, Abdullahi Aliyu; Muhammad, Umar (Sokoto Educational Review, 2014)
The paper attempted to propose a Climate Change Education Curriculum that is conceived to provide a clear understanding of the Climate Change phenomenon for students in Tertiary institutions in Nigeria. Nobody is left in doubt of the relevance of climate change education in Nigeria tertiary education system. Tertiary educational institutions are expected to play a proactive role in proffering solutions to climate change challenges facing Nigeria. What needs to be done is to harness resources toward putting in place a well-articulated climate change education curriculum that should provide requisite information/knowledge and skills for future leaders. Thus, it is recommended that cogent policies need to be developed to ensure that climate change education is fully integrated into tertiary education system in Nigeria; that climate change education curriculum should be offered either as a standalone specialized course or integrated within other courses; and professional development support be provided to educators so as to be able to deliver effectively and also to be able to develop relevant teaching materials on climate change that could stand the test of time.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T13530 Climate Change and Environmental Impact; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Fatalism, Climate Resiliency Training and Farmers’ Adaptation Responses: Implications for Sustainable Rainfed-Wheat Production in Pakistan - Mahmood, Nasir; Arshad, Muhammad Umair; Kaechele, Harald; Shahzad, Muhammad Faisal; Ullah, Ayat; Mueller, Klaus (Sustainability, 2020)
Climate change is a severe threat to the agricultural sector in general and to rainfed farming in particular. The aim of this study was to investigate the factors that can potentially affect the adaptation process against climate change. This study focused on wheat farmers and farming systems in the rainfed agroecological zone of Pakistan. Farmers’ data related to climate change fatalism, the availability of climate-specific extension services, socioeconomic and institutional variables, and farm characteristics were collected. A logit model to assess farmers’ decisions to adopt an adaptation measure and a multinomial logit model to assess their choice of various adaptation measures were used. The results showed that fatalistic farmers were unlikely to implement climate change adaptation measures. The variables related to the climate-specific extension services, including farmers’ participation in training on climate-resilient crop farming and the availability of mobile communication-based advisory services, had highly significant and positive impacts on farmers’ decisions and their choice of adaptation measures. Input market access and tractor ownership also had positive and significant impacts on farmers’ decisions to adapt and their choice of adaptation measures. This study highlights the need to improve rainfed-wheat farmers’ education levels to change their fatalistic attitudes towards climate change. Furthermore, government action is needed to provide climate-specific extension services to ensure sustainable production levels that will ultimately lead to food and livelihood security under a changing climate.
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate resiliency training; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T11886 Risk Management and Vulnerability in Agriculture; openalex:import; openalex:yes

Application of Machine Learning Techniques to Delineate Homogeneous Climate Zones in River Basins of Pakistan for Hydro-Climatic Change Impact Studies - Nusrat, Ammara; Gabriel, Hamza Farooq; Haider, Sajjad; Ahmad, Shakil; Shahid, Muhammad; Jamal, Saad Ahmed (Applied sciences, 2020)
Climatic data archives, including grid-based remote-sensing and general circulation model (GCM) data, are used to identify future climate change trends. The performances of climate models vary in regions with spatio-temporal climatic heterogeneities because of uncertainties in model equations, anthropogenic forcing or climate variability. Hence, GCMs should be selected from climatically homogeneous zones. This study presents a framework for selecting GCMs and detecting future climate change trends after regionalizing the Indus river sub-basins in three basic steps: (1) regionalization of large river basins, based on spatial climate homogeneities, for four seasons using different machine learning algorithms and daily gridded precipitation data for 1975–2004; (2) selection of GCMs in each homogeneous climate region based on performance to simulate past climate and its temporal distribution pattern; (3) detecting future precipitation change trends using projected data (2006–2099) from the selected model for two future scenarios. The comprehensive framework, subject to some limitations and assumptions, provides divisional boundaries for the climatic zones in the study area, suitable GCMs for climate change impact projections for adaptation studies and spatially mapped precipitation change trend projections for four seasons. Thus, the importance of machine learning techniques for different types of analyses and managing long-term data is highlighted.
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T10466 Numerical Weather Prediction Models; openalex:import; openalex:yes